Development of A Flashcard Learning Resource for the Make A Match Cooperative Learning Model in The Ipas Subject, Focusing On The Topic of 'Parts of The Body' for Year 1 Students at Sdn Liprak Kidul 1. - Ririn Rizkana Kamalia; Ludfi Arya Wardana; Faridahtul Jannah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to develop Flashcard learning media based on the cooperative learning model Make a Match on the topic My Body Parts to improve creative thinking skills and learning outcomes of first-grade students at SDN Liprak Kidul I. The study was motivated by students' low interest and learning outcomes, the dominance of lecture-based teaching methods, limited use of engaging learning media, and low creative thinking skills in IPAS learning. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The subjects were 25 first-grade students. Research instruments included media and material expert validation sheets, student response questionnaires, and pretest and posttest learning achievement tests. The results showed that the developed Flashcard media had very high validity, practicality, and effectiveness. The media feasibility reached 94.64% based on media expert validation and 90% based on material expert validation. Student responses showed a practicality score of 94.90%, categorized as very practical. The effectiveness was demonstrated by an increase in the average learning score from 64.00 on the pretest to 91.60 on the posttest. The average N-Gain score was 0.7313, categorized as high. Therefore, Flashcard learning media based on the Make a Match model is valid, practical, and effective for improving student engagement, creative thinking skills, and learning outcomes in IPAS learning.